2021
DOI: 10.1186/s12955-021-01799-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of personal factors in quality of life among Iranian women with vaginismus: a path analysis

Abstract: Background The aim of this study was to provide a path model for assessing the direct and/or indirect effects of psychological/behavioral parameters on health-related quality of life among women with vaginismus. Methods A cross-sectional study was conducted on a sample of 236 women with vaginismus disorder attending to sex clinics in Tehran, Iran from April 2017 to March 2018. Data were collected using a demographic questionnaire, the marital satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…According to the previous studies, the selfreported duration of vaginismus ranges from 3 months to 44 years. 3,[15][16][17] In our study, the mean duration of vaginismus was 19.3 months (range: < 1-96 months). The shorter duration of our study could result from religious and cultural norms where procreation is considered an important aspect; many women approached marriage at an earlier stage.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…According to the previous studies, the selfreported duration of vaginismus ranges from 3 months to 44 years. 3,[15][16][17] In our study, the mean duration of vaginismus was 19.3 months (range: < 1-96 months). The shorter duration of our study could result from religious and cultural norms where procreation is considered an important aspect; many women approached marriage at an earlier stage.…”
Section: Discussionmentioning
confidence: 52%
“…As procreation defines marriage and healthy sexual life, vaginismus affects a couple's emotional health within their marriage; thus, the treatment and improvement of vaginismus are of chief importance. 3,11 As vaginismus contributes to vaginal atrophy and dyspareunia, treating the same to achieve painless and satisfactory intercourse may be beneficial. Considering the physical and behavioral factors, various treatment modalities include cognitive and behavioral therapies, relaxation methods, sex education, vaginal dilation, vaginal desensitization methods like botulinum toxin, local anesthetic agents, psychotherapy or sex therapy, and physiotherapy of pelvic muscles; other invasive methods are ultrasound-guided inter-fascial plane blocks electromyography and biofeedback hypnotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was in contrast with the lack of sexual education described in all the studies. Intimate knowledge was provided by the Internet (Alsubaie, 2019;Velayati, 2021) and reported subjective sexual experiences of friends and families (Tetik et al, 2020), which often were described as traumatic (Karrouri, 2017). Farnam et al (2014), Karrouri (2017), andTetik et al (2020) reported an important association between vaginismus and comorbid anxiety disorders and anxiety traits.…”
Section: Resultsmentioning
confidence: 99%
“…These misconceptions often emanate from the ignorance of the anatomy and physiology of sexual organs and the steps of copulation (Muammar et al, 2015), and being highly educated does not prevent having a distorted conceptualization of sexuality (Farnam et al, 2014; Zgueb et al, 2019). Oftentimes, the only idea that women have about it is one that is given to them by the Internet (Alsubaie, 2019; Velayati, 2021) or by other “more experienced” female friends or family members, who describe how painful the first penetration is (Karrouri, 2017; Tetik et al, 2020). When asked about their perceptions of what might be causing their condition, many list the fear of reproducing the pain of a traumatic event during childhood (Ward and Ogden, 1994), whether it was directed to the pelvis (painful examination, traumatic toilet training, or rape) or to somewhere else (like undergoing surgery on another part of the body) (Ward and Ogden, 1994).…”
Section: Discussionmentioning
confidence: 99%